A fundamental radicalização e racialização da questão social para um projeto profissional antirracista no serviço social - Assis, Eliane Santos de (2022)
The objective of this work is to problematize the notion of social issue that guides the professional work of social workers in Brazil. The motivation for such research stems from a perception that this notion does not include one of the fundamental elements of Brazilian social formation, racism, which limits its scope and historicity. We are based on bibliographic and documentary research that problematizes the social issue and those aimed at the study of race relations and Social Work. We noticed that in the vast majority of these studies the social question views used were basically coined by four authors: Marilda Vilela Iamamoto, Potyara Amazoneida Pereira Pereira, Maria Carmelita Yazbek and José Paulo Netto. We interviewed the 3 authors and the author in order to apprehend which elements moved their lenses away from the analysis of the poignant racial issue that particularizes Brazilian racial relations. This thesis identified that the absences present in consecrated texts of social work were reproduced inseveral studies and in many of the normative documents of professional practice, marking the professional ethical-political project of Social Work, therefore academic training and professional work. On the other hand, we recognize an expressive increase in research and publications that deal with race relations and that can strengthen a professional training and exercise committed to the elimination of all forms of prejudice